ANALYSIS OF THE INFLUENCE OF CONVENIENCE AND BENEFITS OF INFORMATION TECHNOLOGY ON THE PRACTICE OF PHARMACY ELECTRONIC PRESCRIPTION SERVICES IN BANTEN PROVINCE - Dewi Afriliyanti; Maura Linda Sitanggang; Nurita Andayani (SEAN Institute, 2023)
Information technology has become a vital element in the health sector, including pharmaceutical services in pharmacies. The usefulness of information technology in pharmacies, especially electronic prescription services, is highly dependent on the acceptance of pharmacists and pharmaceutical technicians of this information technology. This study aims to analyze the factors that influence the acceptance of pharmacists and pharmacy technicians to information technology which has an impact on the implementation of the practice of electronic prescription services in pharmacies in Banten Province. The research method is cross-sectional using the Technology Acceptance Model which is analyzed using the Structural Equational Model method. There were 222 pharmacists and pharmacy technical personnel (TTK) from pharmacies in 8 cities/districts in Banten Province who responded to the study. The results of the multivariate test of the structural model show that 4 of the 5 hypotheses are proven. Perceived convenience is proven to have a positive effect on acceptance of information technology and the practice of electronic prescription services in pharmacies (coefficient value 0.618). Meanwhile, perceived benefits only proved to have a significant positive effect on acceptance of information technology (coefficient value 0.328), not on the practice of electronic prescription services at pharmacies (coefficient value -0.131), although it turned out that the attitude constructs of acceptance of information technology by pharmacists and TTK had a positive effect on practice of electronic prescription services in pharmacies (coefficient value 0.353). The research findings are expected to provide insight into the relationship of influencing factors and practical implications regarding perceived behavior from the use of information technology. This study is also expected to be the basis for the first national study conducted on pharmacists and TTK regarding user attitudes towards technology and its impact on electronic prescription services in pharmacies.